Unraveling Interactions Between Anesthetics and the Endothelium: Update and Novel Insights. (February 2016) - Aguirre, José A.; Lucchinetti, Eliana; Clanachan, Alexander S.; Plane, Frances; Zaugg, Michael
Abstract : The vascular endothelium is one of the largest organs in the body and consists of a single layer of highly specialized cells with site-specific morphology and functions. Endothelial cells play a vital role in the regulation of vascular tone in arterial, venous, microvascular, and lymphatic vascular beds. The endothelium also coordinates angiogenesis and controls cell adhesion, fluid homeostasis, and both innate and adaptive immunity. Fundamental research has shown that general and local anesthetics markedly modulate the biological activities of endothelial cells under aerobic and ischemia-reperfusion conditions, making the endothelium an important target of anesthetics in the cardiovascular system. Halogenated volatile anesthetics provide significant anti-inflammatory actions and protect the endothelium against ischemia-reperfusion injury, despite their inhibiting effects on endothelium-dependent vasorelaxation. They provide not only acute but also potential long-term, beneficial effects. Although many effects of IV anesthetics on endothelial function are controversial, or completely unexplored, propofol and opioids appear to have the most favorable profile with respect to the preservation of endothelial function. Some opioids and ketamine have stereoselective effects on the endothelium. Finally, there is experimental evidence to suggest important effects of anesthetics on the regulation of vascular permeability, proliferation of stem cells, including endothelial progenitor cells, and promotion or inhibition of tumor growth, potentially related to alterations in angiogenesis. However, most of these findings are from in vitro experiments and await confirmation in an in vivo setting. Thus, the clinical implications of these interactions remain uncertain.